Clinic morphological features of Goodpasture’s syndrome manifested with respiratory disorders - Yu. M. Mostovoy; A. V. Demchuk; T. V. Konstantynovych; N. O. Pentiuk; L. V. Blazhevska (Patologìâ)
Goodpasture’s syndrome is one of rare pathological conditions. It stipulates problem of timely diagnostics and prescription of early pathogenic therapy for cessation of progressive autoimmune inflmmation and safe of patient’s life. Presented clinical case demonstrates diffilties of recognizing Goodpasture’s syndrome in case of its debut with dominating symptoms and signs of bacterial affction of the lungs and severe respiratory failure. Case presentation. We described case of Goodpasture’s syndrome in the middle-aged woman (54 years old) which began from symptoms of community-acquired pneumonia, hemoptysis and fiished tragically with developing severe respiratory and renal failures. Conclusions. Management of community-acquired pneumonia patient, who has recurrent hemoptysis, minimal changes of the urinary system, who does not give adequate answer to the antibiotic treatment, must include additional investigation for revealing immunological systemic genesis of pulmonary tissue injury. It improves prognosis by virtue of early use adequate pathogenic therapy.